Dry matter partitioning, yield and grain protein content of fine aromatic boro rice (cv. BRRI dhan50) in response to nitrogen and potassium fertilization (Bangladesh Journal of Botany, 2021)
An experiment was conducted to study dry matter partitioning, yield and grain protein content of fine aromatic Boro rice (cv. BRRI dhan50) in response to nitrogen and potassium fertilization. The experiment consisted of four levels of nitrogen viz., 0, 50, 100 and 150 kg/ha and four levels of potassium viz., 0, 30, 60 and 90 kg/ha. The results revealed that at growth stage, the highest total dry matter partitioning and accumulation were obtained from 150 kg N/ha along with 90 kg K/ha at physiological maturity stage. At harvest, the highest number of tillers/hill (8.58), number of grains/panicle (113.9), grain yield (5.15 t/ha) and grain protein content (8.30%) were obtained from 100 kg N/ha along with 90 kg K/ha. Total dry matter partitioning and accumulation were greatly influenced by the application of 150 kg N/ha along with 90 kg K/ha. Application of 100 kg N/ha along with 90 kg K/ha interaction appeared as the promising practice in fine aromatic rice (cv. BRRI dhan50) cultivation in terms of yield and grain protein content.